Identification of metabolizing enzyme genes associated with xenobiotics and odorants in the predatory stink bug Arma custos based on transcriptome analysis - Wenhong Li; Jingmiao Zou; Xiang Yang; Mingwei Yang; Po Jiang; Xinyi Wang; Chunyang Huang; Yueping He (Heliyon, 2023)
The predatory stink bug, Arma custos, is a highly effective beneficial predator of crop pests. The lack of gene information related to xenobiotic detoxification and odorant degrading enzymes in the predator stink bugs to date has limited our ability for more in-depth studies of biological control. Hence, we conducted de novo assembly of the A. custos transcriptome from guts, antennae, and other tiussue samples of 5th instar larvae using Illumina sequencing technology. A total of 91, 50 and 23 genes of cytochrome P450 monooxygenases (CYPs), carboxyl/choline esterases (CCEs) and glutathione S-transferases (GSTs) genes were identified, respectively. Gene expansions of CYP3 and CYP4 clans and the hormone and pheromone processing CCE class were found in A. custos. Analysis of tissue-specific expression patterns showed that 37 CYPs, 14 CCEs and 8 GSTs were enriched in guts, and 6 CYPs, 5 CCEs and 2 GSTs were up-regulated in antennae, suggesting their potential roles on xenobiotics detoxification and ordorant degradation. Gene information data presented here could be useful for a deeper understanding of the ecology, physiology and behavior of this beneficial species and could be helpful to improve their bio-control efficiency.